Newborn Screening for Five Conditions in a Tertiary Care Government Hospital in Bengaluru, South India—Three Years Experience. (10th December 2019) - Kommalur, Anitha; Devadas, Sahana; Kariyappa, Mallesh; Sabapathy, Sarala; Benakappa, Asha; Gagandeep, Vijayalaxmi; Veranna Sajjan, Sushma; Krishnapura Lakshminarayana, Shilpa; Dakshayani, B; Devi Chinnappa, Gayathri
Abstract: Purpose: Newborn screening is the need of the hour in a developing country like India as there is paucity of data from studies conducted in government hospitals with large sample size. The purpose of the study is to estimate incidence rate and recall rates for five conditions screened in the neonatal period namely congenital hypothyroidism, congenital adrenal hyperplasia, glucose-6-phosphate dehydrogenase (G6PD) deficiency, galactosemia and phenyl ketonuria (PKU). Methods: The study was conducted at VaniVilas Hospital attached to Bangalore Medical College and Research Institute. A retrospective analysis of the results of newborn screening programme during a 3-year period between January 2016 and December 2018 was done. There were 47 623 livebirths during this period out of which 41 027 babies were screened (coverage—86% of total livebirths). Heelprick samples after 48 h of life and prior to discharge were analysed by quantitative assessment. Neonates having positive screening results were recalled by telephonic call for repeat screening and confirmatory tests. Results: G6PD deficiency was the most common disorder with an incidence of 1:414, followed by congenital hypothyroidism and Congenital Adrenal Hyperplasia with an incidence of 1:2735 and 1:4102, respectively. Galactosemia and PKU were found to be rare in our population. The overall average recall rate was 0.6% which meant that 24 normal newborns were recalled for testing for one confirmed case. The recall rate was relatively higher for galactosemia and G6PD deficiency which was at 0.25% each compared to the other conditions where it was below 0.05%. Conclusion: The results of the study emphasize the need for universal newborn screening especially in all government hospitals with large birth cohorts.